Lipid-Coated MCM-41 Mesoporous Silica Nanoparticles Loaded with Berberine Improved Inhibition of Acetylcholine Esterase and Amyloid Formation - Singh A.K.; Singh S.S.; Rathore A.S.; Singh S.P.; Mishra G.; Awasthi R.; Mishra S.K.; Gautam V.; Singh S.K. (My University, 2025)
Selective permeability of the blood-brain barrier limits effective treatment of neurodegenerative disorders. In the present study, brain-targeted lipid-coated mesoporous silica nanoparticles (MSNs) containing berberine (BBR) were synthesized for the effective treatment of Alzheimer's disease (AD). The study involved synthesis of Mobil Composition of Matter-41 (MCM-41) mesoporous silica nanoparticles (MSNs), BBR loading, and lipid coating of MSNs (MSNs-BBR-L) and in vitro and in vivo characterization of MSNs-BBR-L. The liposomes (for lipid coating) were prepared by the thin-film hydration method. Transmission electron microscopy (TEM) images indicated 5 nm thickness of the lipid coating. Dynamic light scattering (DLS) and TEM results confirmed that the size of synthesized MSNs-BBR-L was in the range of 80-100 nm. The X-ray diffraction (XRD) pattern demonstrated retention of the ordered structure of BBR after encapsulation and lipid coating. Fourier transform infrared (FTIR) spectrum confirmed the formation of a lipid coat over the MSN particles. MSNs-BBR-L displayed significantly (p < 0.05) higher acetylcholine esterase (AChE) inhibitory activity. The study confirmed significant (p < 0.05) amyloid fibrillation inhibition and decreased the malondialdehyde (MDA) level by MSNs-BBR-L. Pure BBR- and MSNs-BBR-L-treated AD animals showed a significant decrease in the BACE-1 level compared to scopolamine-intoxicated mice. Eight times higher area under the curve for MSNs-BBR-L (2400 ± 27.44 ng h/mL) was recorded compared to the pure BBR (295.5 ± 0.755 ng h/mL). Overall, these results highlight the utility of MSNs-BBR-L as promising drug delivery vehicles for brain delivery of drugs. © 2021 American Chemical Society.